Pengaruh Kepuasan dan Switching Barries Terhadap Loyalitas Pelanggan Telkomsel Pada Karyawan PT. Gistek Majalengka (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2020)
This research was conducted at the PT. Gistek Majalengka The background of this research isthe decrease in satisfaction with telkomsel which results in a decrease in the number ofcustomers. To determine the effect of satisfaction and switching barriers on Telkomsel customerloyalty, either partially or simultaneously. In this study the authors used a survey method witha descriptive analysis approach and verification. The population used was all employeesMajalengka with a sample of one hundred people. The data collection technique is done bydistributing questionnaires. The data analysis design used Classical Assumption Test, MultipleLinear Regression Analysis, Analysis of the Coefficient of Determination, Hypothesis Test witht test and f test. The results of this study indicate that satisfaction is in the good category.Switching barriers are in the good category. Customer loyalty is in a good category.Satisfaction has a significant effect on customer loyalty. Switching barrier has a significanteffect on customer loyalty. Satisfaction and switching barriers together have a significant effecton customer loyalty.